Occupational stressors experienced by police officers during Coronavirus disease (Covid-19) outbreak – a systematic literature review - Mohamed, Noradila; Zainal Abidin, Emilia; Rasdi, Irniza; Ismail, Zitty Sarah; Ismail, Noor Hassim (UPM Press, 2021)
Introduction: Police officers are at high risk for many forms of psychological problems which includes anxiety and depression during COVID-19 outbreak. This review is aimed to identify relevant stress factors faced by police officers during COVID-19. Methods: Literature searches were conducted in Scopus and Web of Science databases. Search terms used includes the following: psychological OR stress OR mental health, and COVID-19 OR coronavirus, and police, OR policing OR law enforcement. Results: All types of articles published in January 2020-October 2020 which were relevant to the subject of the review were identified. The stress factors found relevant can be divided into operational, organizational, and other factors. Risk of infection, lack of knowledge on disease, uncertainty, availability of safety gear, and lack of pre-disaster training are the unique stress factors related to COVID-19. Conclusion: It is crucial to determine pandemic-specific occupational stressors experienced by police officers to enable its mitigation and improve work performance. Recommended risk control may include counseling services to officers affected by COVID-19, improve officers job satisfaction by acknowledging their work, and provide social support to maintain their wellbeing.